Paediatrics: how to manage septic shock - Kam Lun Hon; Karen Ka Yan Leung; Felix Oberender; Alexander KC Leung (BioExcel Publishing Ltd, 2021)
Background: Septic shock is a common critical illness associated with high morbidity and mortality in children. This article provides an updated narrative review on the management of septic shock in paediatric practice. Methods: A PubMed search was performed using the following Medical Subject Headings: "sepsis", "septic shock" and "systemic inflammatory response syndrome". The search strategy included meta-analyses, randomized controlled trials, clinical trials, observational studies and reviews. The search was limited to the English literature and specific to children. Results: Septic shock is associated with high mortality and morbidity. The outcome can be improved if the diagnosis is made promptly and treatment initiated without delay. Early treatment with antimicrobial therapy, fluid therapy and vasoactive medications, and rapid recognition of the source of sepsis and control are the key recommendations from paediatric sepsis management guidelines. Conclusion: Most of the current paediatric sepsis guideline recommendations are based on the adult population; therefore, the research gaps in paediatric sepsis management should be addressed.